Antibody Specificity Following a Recent Bordetella pertussis Infection in Adolescence Is Correlated With the Pertussis Vaccine Received in Childhood - Raeven, René H. M.; van der Maas, Larissa; Pennings, Jeroen L. A.; Fuursted, Kurt; Jørgensen, Charlotte Sværke; van Riet, Elly; Metz, Bernard; Kersten, Gideon F. A.; Dalby, Tine (Frontiers in Immunology, 2019)
Bordetella (B.) pertussis resurgence affects not only the unvaccinated, but also the vaccinated population. Different vaccines are available, however, it is currently unknown whether the type of childhood vaccination has an influence on antibody responses following a B. pertussis infection later in life. Therefore, the study aim was to profile serum antibody responses in young adults with suspected B. pertussis infections, immunized during childhood with either whole-cell (wPV) or monocomponent acellular pertussis (aPV) vaccines. Serum anti-pertussis toxin (PTx) IgG antibody levels served as an indicator for a recent B. pertussis infection. Leftover sera from a diagnostic laboratory from 36 Danish individuals were included and divided into four groups based on immunization background (aPV vs. wPV) and serum anti-PTx IgG levels (- vs. +). Pertussis-specific IgG/IgA antibody levels and antigen specificity were determined by using multiplex immunoassays (MIA), one- and two-dimensional immunoblotting (1&2DEWB), and mass spectrometry. Besides enhanced anti-PTx levels, wPV(+) and aPV(+) groups showed increased IgG and IgA levels against pertactin, filamentous hemagglutinin, fimbriae 2/3 and pertussis outer membrane vesicles (OMV). In the wPV(-) and aPV(-) groups, only low levels of anti-OMV antibodies were detected. 1DEWB demonstrated that antibody patterns differed between groups but also between individuals with the same immunization background and anti-PTx levels. 2DWB analysis for serum IgG revealed 133 immunogenic antigens of which 40 were significantly different between groups allowing to differentiate wPV(+) and aPV(+) groups. Similarly, for serum IgA, 7 of 47 immunogenic protein spots were significantly different. This study demonstrated that B. pertussis infection-induced antibody responses were distinct on antigen level between individuals with either wPV or aPV immunization background. Importantly, only 2DEWB and not MIA could detect these differences indicating the potential of this method. Moreover, in individuals immunized with an aPV containing only PTx in childhood, the infection-induced antibody responses were not limited to PTx alone.